CHANGE OF ORGANIZATIONAL CULTURE OF THE ENTERPRISE AS OVERCOMING OF DIGITAL TRANSFORMATION RESISTANCE - H. Menin (Вестник университета)
Change of organizational culture in the conditions of digital transformation, which is a mandatory requirement in almost every industry, has been considered. The change of organizational culture correlates with the beginning of building a «new» organization, that is able to respond flexibly to transformational changes and has experience in resolving crisis situations. The main elements, that define digital culture: risk, short-term planning and transformation of organizational culture, cooperation and destruction, have been highlighted. The difficulties, that arise in the process of digital transformation of organizational culture have been noted, among them are: the traditional culture of the company, cost overruns on infrastructure, limited scalability, inefficient automation and problems of professional development. The values, that digital culture brings to the organization have been studied: it provides flexibility of mind and hand-eye coordination in the working process of the organization, eliminates hierarchy, involves each employee in the decision-making process, uses the skills of employees and increases their abilities, attracts talented personnel to the organization. The areas to achieve changes in organizational culture in modern conditions of digital transformation have been allocated.